International Olympic Committee consensus statement on pain management in elite athletes - Hainline, B.; Derman, W.; Vernec, A.; Budgett, R.; Deie, M.; Dvorák, J.; Harle, C.; Herring, S. A.; McNamee, M.; Meeuwisse, W.; Lorimer M. G.; Omololu, B.; et al. (British Journal of Sports Medicine, 2017)
Pain is a common problem among elite athletes and is frequently associated with sport injury. Both pain and injury interfere with the performance of elite athletes. There are currently no evidence-based or consensus-based guidelines for the management of pain in elite athletes. Typically, pain management consists of the provision of analgesics, rest and physical therapy. More appropriately, a treatment strategy should address all contributors to pain including underlying pathophysiology, biomechanical abnormalities and psychosocial issues, and should employ therapies providing optimal benefit and minimal harm. To advance the development of a more standardised, evidence-informed approach to pain management in elite athletes, an IOC Consensus Group critically evaluated the current state of the science and practice of pain management in sport and prepared recommendations for a more unified approach to this important topic.